Evaluasi Performansi Video Games Ditinjau Dari Aspek Usability (Studi Kasus : Game Pro Evolution Soccer (PES) 2011) - Lusi Susanti; Angga Baresky (UIN Sultan Syarif Kasim Riau, 2012)
HCI is a study of planning and designing computer systems that aims to help human activities more productive and safe when interacting with computer (Preece, 1994). HCI leads to the design of computer systems which is suitable for user’s needs, commonly known as usability. Usability helps systems easy to use and to learn either by individuals or groups. The research is conducted to analyze and evaluate the usability of video games. There are ten usability principles made by Nielsen (1993). However, only eight principles are relevant to be used as variables in evaluating the usability of games. This study uses a questionnaire as a research instrument with a Likert scale as the scale of measurement.Results show that from eight usability variables, video games meet the 7 from 8 variables of usability indicated that video games are generally usable. In order to increase usability, convenience, and satisfaction of video games, it’s recommended to improve